Assessment of Role in Non-Governmental Organizations and Their Humanitarian Effort in Refugee Camps Worldwide - Balidemaj, Festina; Balidemaj, Albina (European Journal of Social Science Education and Research, 2022)
The relief and humanitarian effort of non-governmental organizations (NGOs) in refugee camps worldwide requires prompt, coordinated, and effective interventions. As evident by the physicians and nurses make up of NGOs, a significant portion of such effort is focused on health care issues such as treating, managing, and preventing the spread of infectious diseases of refugees. In this literature-based project, the role of pharmacists in the relief efforts of NGOs is examined. Currently, pharmacists represent a small fraction ( 9 percent) of the non-governmental organizations’ task force, which undermines the invaluable potential of their contributions to the relief efforts. Student pharmacists should also be introduced to the role of non-governmental organizations’ humanitarian efforts and the world of opportunities available in helping people under stress while being exposed to different cultures towards their own professional growth.